2021
DOI: 10.1016/j.kint.2020.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic pathogenic variations in DNAJB11 cause Ivemark II syndrome, a renal-hepatic-pancreatic dysplasia

Abstract: The Nijmegen Biomedical Study is a population-based cross-sectional study conducted in the eastern part of the Netherlands. As part of the overall study, we provide reference values of estimated glomerular filtration rate (GFR) for this Caucasian population without expressed risk. Age-stratified, randomly selected inhabitants received a postal questionnaire on lifestyle and medical history. In a large subset of the responders, serum creatinine was measured. The GFR was then measured using the abbreviated Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The mutation was shown to cause tortuous primary cilia in renal tubules in the fetus. Renal and cardiac features of the fetus were smiliar to our cases; however, pancreatic and hepatic findings were not mentioned in the autopsy report [Jordan et al, 2021].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The mutation was shown to cause tortuous primary cilia in renal tubules in the fetus. Renal and cardiac features of the fetus were smiliar to our cases; however, pancreatic and hepatic findings were not mentioned in the autopsy report [Jordan et al, 2021].…”
Section: Discussionsupporting
confidence: 53%
“…While preparing this paper, Jordan et al [2021] reported a fetus diagnosed with renal-hepatic-pancreatic dysplasia with a homozygous c.600-2A>C splice site mutation in DNAJB11. The mutation was shown to cause tortuous primary cilia in renal tubules in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic Class 4 or 5 variants were identified in NPHP3 in one case with ductal plate anomaly, in CEP290 in one case with postaxial polydactyly, in TMEM67 in one case with occipital encephalocele, and in DNAJB11 in one case with renal, hepatic, and pancreatic dysplasia that was reported elsewhere (Jordan et al, 2020).…”
Section: Cases With a Ciliopathy Like A Phenotypementioning
confidence: 80%
“…Heterozygous PKD1 variants are the most common cause of adult‐onset autosomal dominant polycystic kidney disease, while biallelic PKD1 variants are associated with early and potentially neonatal‐onset, severe polycystic kidney disease (Al‐Hamed et al, 2019 ; Audrézet et al, 2016 ; Durkie et al, 2021 ). Heterozygous DNAJB11 variants are associated with autosomal dominant polycystic kidney disease, while biallelic variants cause Ivemark II syndrome or renal‐hepatic‐pancreatic dysplasia syndrome (Jordan et al, 2021 ). We propose that TOPORS has similar properties, with heterozygous variants causing the milder, organ‐specific ciliopathy retinitis pigmentosa, and biallelic variants causing OFDS‐spectrum syndromic ciliopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The axoneme (blue) is composed of microtubule doublets that provides structure to the cilium and also forms the framework for ciliary transport. The nucleus (orange) is an important target of ciliary signaling (EHZ) [Color figure can be viewed at wileyonlinelibrary.com]Hamed et al, 2019;Audrézet et al, 2016;Durkie et al, 2021).Heterozygous DNAJB11 variants are associated with autosomal dominant polycystic kidney disease, while biallelic variants cause Ivemark II syndrome or renal-hepatic-pancreatic dysplasia syndrome(Jordan et al, 2021). We propose that TOPORS has similar properties, with…”
mentioning
confidence: 99%